DIGITAL TRANSFORMATION OF THE FINANCE SECTOR IN ZAKAT MANAGEMENT ORGANIZATIONS CAN AFFECT THE INCREASE IN PUBLIC PREFERENCES IN DONATING (CASE STUDY IN BANJARBARU CITY) - Mairijani Mairijani; Wahyu Hidayat; Rizky Fadhillah; Andriani Andriani (ADISAM Publisher, 2025)
Digital transformation is currently accelerating, especially in the financial sector, with this progress many parties take advantage of it to offer the public convenience in transactions, including by zakat management organizations. This study aims to examine the effect of digital transformation on preferences for donating to zakat management organizations (case study of people in Banjarbaru City). This research uses quantitative method with descriptive approach. Data were collected through questionnaires distributed to 102 respondents who had previously donated digitally in the Banjarbaru. Based on the results of the partial test (t-test), the calculated t-value was greater than the t-table value (10.707 > 2.569), with a significance level of (0.000 < 0.05). This indicates that digital transformation has a positive and significant effect on public preferences in donating through Zakat Management Organizations (OPZ). The average score for the digital transformation variable fell into the high category, with the ease of access indicator scoring the highest (4.05), followed by benefits, convenience, security, and speed. Meanwhile, for the public preference variable, the institutional credibility indicator scored the highest (4.16), followed by self-motivation and social motives. These results indicate that the use of digital technology has a significant impact on people's preferences in donating, especially to zakat management organizations.